2019
DOI: 10.9734/ajrimps/2019/v7i430126
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Molecular Studies on the Role of Rosemary (Rosmarinus officinalis) Extract in Reducing Liver and Kidney Toxicity Due to Etoposide in Male Rats

Abstract: Aims: Etoposide (Vepesid) is chemotherapeutic drugs that inhibit topoisomerase II activity and long been used for treatment of human malignancies, where it is a semi-synthetic compound derived from the plant Podophyllum peltatum. The current study was designed to investigate the possible protective effect of rosemary extract against Etoposide -induced changes in liver and kidney functions, and DNA damage in rats. Materials and Methods: A total of 50 male Wistar albino rats were divided randomly into four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…In our experiments, we found that the ALT, AST, and LDH were significantly lower in Group 3 compared with Group 2. This results is in agreement with the findings of Karataş et al [25], and Almakhatreh et al [26]. R. Officinalis extract greatly lowered the blood-brain barrier permeability disruption and injuries, moreover, it lessens the effect of the myocardial infarction and neurological deficit scores after focal Ischemia-Reperfusion.…”
Section: Resultssupporting
confidence: 93%
“…In our experiments, we found that the ALT, AST, and LDH were significantly lower in Group 3 compared with Group 2. This results is in agreement with the findings of Karataş et al [25], and Almakhatreh et al [26]. R. Officinalis extract greatly lowered the blood-brain barrier permeability disruption and injuries, moreover, it lessens the effect of the myocardial infarction and neurological deficit scores after focal Ischemia-Reperfusion.…”
Section: Resultssupporting
confidence: 93%
“…According to numerous studies, plant ingredients and their extracts were used in anticancer, anti‐inflammation, reducing renal and hepatotoxicity, and treat many diseases . Vitamin B17 (VB17), amygdalin and formerly called laetrile is one of many nitrilosides which are natural cyanide containing substances, which is abundant in the seeds of Prunasins family, such as apricots, apples, almonds, peaches, and other rosaceous plants .…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15][16] According to numerous studies, plant ingredients and their extracts were used in anticancer, anti-inflammation, reducing renal and hepatotoxicity, and treat many diseases. [17][18][19][20][21] Vitamin B17 (VB17), amygdalin and formerly called laetrile is one of many nitrilosides which are natural cyanide containing substances, which is abundant in the seeds of Prunasins family, such as apricots, apples, almonds, peaches, and other rosaceous plants. 22,23 VB17 consists of two molecules of glucose, one of them is benzaldehyde which induces an analgesic action, the second is hydrocyanic acid which is an antineoplastic compound and used to treat the tumor and relieve pain.…”
mentioning
confidence: 99%
“…Chemotherapeutic treatment of rhabdomyosarcoma includes the use of agents such as doxorubicin, vinblastine, and etoposide. Combination of these drugs with rosemary extracts allowed to diminish the concentration of the chemical agent, thus reducing its toxic effects [ 45 , 54 ]. Regarding the cytotoxic activity of R. officinalis on rhabdomyosarcoma cell lines, there is lack of literature data.…”
Section: Discussionmentioning
confidence: 99%